Exact mass analysis of sulfur clusters upon encapsulation by a polyaromatic capsular matrix - Sho Matsuno (Nature Portfolio, 2017)
The structures of inorganic clusters are commonly characterized by mass spectrometry (MS), but neutral sulfur clusters heavily fragment under MS conditions, preventing their exact mass determination. Here, the authors successfully perform MS on labile cyclic sulfur clusters by stabilizing them within ionic supramolecular capsules.